Following phospholipid transfer through the OmpF 3 –MlaA–MlaC lipid shuttle with native mass spectrometry - Carla Kirschbaum; Jack L. Bennett; Qiaoyu Tian; Navoneel Sen; Iain P. S. Smith; Di Wu; Justin L. P. Benesch; Syma Khalid; Georgia Isom; Carol V. Robinson (Proceedings of the National Academy of Sciences, 2025)
The maintenance of lipid asymmetry (Mla) system in gram-negative bacteria transfers phospholipids between the outer and inner membrane to maintain the outer membrane asymmetry. Misplaced phospholipids are extracted from the outer leaflet of the outer membrane by MlaA, transferred to the periplasmic lipid transporter MlaC, and shuttled to the inner membrane. We set out to investigate the lipid transfer between MlaA and MlaC using native mass spectrometry, with the aim of determining the lipid preferences of MlaC and whether MlaA preselected lipids for MlaC. First, we characterized the lipids that copurified with overexpressed MlaC, phosphatidylglycerol (PG), and phosphatidylethanolamine (PE), and following delipidation noted a headgroup-independent enrichment of cyclopropane lipids. Under native expression conditions, we found that PG is three-fold enriched on MlaC compared to its abundance in the membrane. Next, we isolated and characterized OmpF 3 –MlaA complexes and demonstrated their ability to enhance loading of delipidated MlaC with bacterial and nonbacterial phospholipids. We then captured the intact ternary lipid shuttle (OmpF 3 –MlaA–MlaC) and demonstrated that PG dissociates this transient complex, releasing lipid-bound MlaC. Together our results point to a high population of endogenous PG on periplasmic MlaC, which likely arises from disassembly of the lipid shuttle to maintain lipid asymmetry for cell viability.